4. Identification of a mutation in a Vietnamese family with autosomal dominant polycystic kidney disease using whole exome sequencing - Anh, Nguyen Tho; Huong, Tran Thị Thu; Tung, Do Dinh; Hai, Nong Van; Duong, Nguyen Thuy (Tạp chí Nghiên cứu Y học, 2023)
Autosomal dominant polycystic kidney disease (ADPKD) is a form of polycystic kidney disease (PKD) in which cysts develop within the kidneys, causing the kidneys to enlarge and lose function over time. ADPKD is caused by mutations in two major genes: PKD1 and PKD2. By whole exome sequencing (WES), we identified a heterozygous missense PKD1 variant (NM_001009944: c.10529C>T, p.T3510M) in a proband from a 2-generation Vietnamese family, in which the proband presented a bilateral renal enlargement and multiple bilateral renal cysts. The segregation of this known mutation was confirmed using Sanger sequencing. The proband and his affected mother were carriers for the mutation, while his father and his sister were wild types. The findings of this study enable doctors to comprehend the underlying genetic cause of polycystic kidney disease and elect appropriate treatment for the patients.